Reformation of Criminal Justice System of Pakistan - Muhammad Arif Rajput; Farid Samir Benavides-Vanegas (European Scientific Journal, ESJ, 2022)
This paper analyzes the loopholes and faults in the Criminal Justice System of Pakistan (CJSP), which is under rising criticism for its ineffectiveness and has been ranked at 108th of the total 139 countries of the world in the Rule of Law Index, 2021. The poor and defective investigation by the police, without any effective prosecutorial or judicial supervision over the process of investigation, is mainly responsible for crippling the CJSP adversarial system, which needs to be reformed to make it effective. A comparative analysis will show that Latin American countries such as Chile, Argentina, México and Colombia have moved from an inquisitorial to an accusatorial system, claiming that this is the best way to protect fundamental rights and to reduce the ever-increasing impunity in these countries. By applying a comparative approach, it shows that both inquisitorial and adversarial system of justice have systematic weaknesses and strengths in their composition. This certainly has motivated the International Criminal Court (ICC), China, Spain, Italy and many other countries to develop an Adquisitorial System-mixed inquisitorial/adversarial system- to get the benefit of best practices of both the systems. The Pakistan case, in relation to the Latin American one, shows that what is important is not to analyze the system in the abstract, but to determine which one solves in a better way the problem a judicial system has: in Pakistan, law and order, given the limitations of police action; in Latin America, the protection of fundamental rights during the criminal process. The case in Pakistan shows that the problems the judicial system is facing can be solved by appealing to a combination of inquisitorial and accusatorial features. This paper concludes suggesting that the existing investigation phase of the CJSP should be transformed, by legal transplant, to an inquisitorial pre-trial investigation process, with necessary modifications, led by the investigative judge while the trial phase remains to be adversarial.